A Guide to the SQL Standard / A User's Guide to the Standard Relational Language SQL - Darwen Hugh; Date C.J (Addison-Wesley Publishing Company, 1994)
SQL2, officially known as International Standard Database Language SQL (1992), represents a major set of extensions to the earlier SQL standard. Introduction, An Overview of SQL, Some Preliminaries, Catalogs and Schemas, Connections and Sessions and Transactions, Data Definition and Manipulation, Data Definition: Domains and Base Tables, Table Expressions, Conditional Expressions, Views, Data Control, Integrity, Security, Advanced Topics, Dates and Times, Temporary Tables, Character Data, Dynamic, The Information Schema, Exception Handling, Appendixes, References and Bibliography, Index.